2005
DOI: 10.1099/jmm.0.45994-0
|View full text |Cite
|
Sign up to set email alerts
|

Activity of moxifloxacin against Bacteroides fragilis and Escherichia coli in an in vitro pharmacokinetic/pharmacodynamic model employing pure and mixed cultures

Abstract: The objective of this study was to determine the pharmacodynamic (PD) activity of moxifloxacin against four selected Bacteroides fragilis strains (three strains with low MICs and one strain with a high MIC) and two Escherichia coli strains (one strain with a low MIC and one strain with a high MIC) in a pharmacokinetic (PK) in vitro model in pure cultures as well as in mixed cultures. PK/PD assays of moxifloxacin were carried out with an initial maximum concentration of 4 . 0 mg l À1 and a half-life of 13 h. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
(25 reference statements)
1
7
0
2
Order By: Relevance
“…Throughout 24 h simulation, the predicted concentration of moxifloacin in abdominal viscera exceeded the in vitro MICs of moxifloxacin for the pathogens commonly isolated in intra-abdominal infections, which have been reported as ≤1 μg/mL for a variety of Gram-negative and Gram-positive organisms [32]. In our study, moxifloxacin achieved high concentrations in abdominal viscera (liver 11.81 μg/mL; kidney 12.53 μg/mL; spleen 10.43 μg/mL), which indicated that it could play a good antibacterial activity in the abdominal cavity and that was in accordance with moxifloxacin clinical use in the treatment of intra-abdominal infection and was supported by the finding that moxifloxacin was effective in an in vitro pharmacokinetic-pharmacodynamic model with mixed aerobic (E. coli) and anaerobic (B. fragilis) strains [33].…”
Section: Discussionsupporting
confidence: 57%
“…Throughout 24 h simulation, the predicted concentration of moxifloacin in abdominal viscera exceeded the in vitro MICs of moxifloxacin for the pathogens commonly isolated in intra-abdominal infections, which have been reported as ≤1 μg/mL for a variety of Gram-negative and Gram-positive organisms [32]. In our study, moxifloxacin achieved high concentrations in abdominal viscera (liver 11.81 μg/mL; kidney 12.53 μg/mL; spleen 10.43 μg/mL), which indicated that it could play a good antibacterial activity in the abdominal cavity and that was in accordance with moxifloxacin clinical use in the treatment of intra-abdominal infection and was supported by the finding that moxifloxacin was effective in an in vitro pharmacokinetic-pharmacodynamic model with mixed aerobic (E. coli) and anaerobic (B. fragilis) strains [33].…”
Section: Discussionsupporting
confidence: 57%
“…Bactericidal effects are observed against most anaerobic pathogens by 24-48 h at concentrations that are 2-4 times their respective MIC [25,40,41]. In mixed cultures of B. fragilis with Escherichia coli or Enterococcus faecium, the bactericidal activity of trovafloxacin and moxifloxacin against B. fragilis was found to be diminished, compared with the activity of these fluoroquinolones against pure cultures of B. fragilis [42,43].…”
Section: Microbiological Activitymentioning
confidence: 88%
“…Throughout 24 h simulation, the predicted concentration of moxifloacin in abdominal viscera exceeded the in vitro MICs of moxifloxacin for the pathogens commonly isolated in intra-abdominal infections, which have been reported as ≤1 µg/mL for a variety of Gram-negative and Gram-positive organisms [32]. In our study, moxifloxacin achieved high concentrations in abdominal viscera (liver 11.81 µg/mL; kidney 12.53 µg/mL; spleen 10.43 µg/mL), which indicated that it could play a good antibacterial activity in the abdominal cavity and that was in accordance with moxifloxacin clinical use in the treatment of intra-abdominal infection and was supported by the finding that moxifloxacin was effective in an in vitro pharmacokinetic-pharmacodynamic model with mixed aerobic ( E. coli ) and anaerobic ( B. fragilis ) strains [33]. …”
Section: Discussionmentioning
confidence: 66%